REM-BEKAS (REVOLUSI MENTAL BERBASIS KONSELING SPRITUAL TEISTIK): Upaya Membangun Generasi Berkarakter FAST (Fathonah, Amanah, Siddiq, dan Tabligh) - DARIMIS DARIMIS (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
It is a fact that good values as well as Islamic velues are dicreased in the recent year. It could be caused by several reasons such as the act of amoral and anarchis. In order to overcome this problem, wholistical approach could be used. One of the approaches is using spiritual teistic counselling. This approach is based on Islamic values which derived from prophetic character. It developes one’s natural tendency (fitrah), critical thinking, and attitude in parallel with Islamic value. The use of this approach produces good character generation who own FAST character (fatonah- smart, amanah- reliable, siddiq-true, and tabligh-deliver).Kata kunci: revolusi mental, konseling spritual teistik, karakter FAST.